Lexical and Contextual Variability of Idiomatic Phrasal Verbs in Harry Potter and the Deathly Hallows Movies - Ghofar Romli, Hairus Salikin (ELLITE, 2016)
The popularity of Harry Potter and the Deathly Hallows (HPDH) as a novel is almost accentuated in the movie version. However, the fascination of watching the movies may be interrupted by the problems arising from the use of some problematic expressions in the original language, especially idiomatic phrasal verbs (IPVs). This paper undergoes some procedures of the analysis starting from the process of data collection, progressing to selection, filtering, and labeling. It extracts PVs in HPDH (97 in HPDH part one and 70 in part two)using linguistic concepts of PV. Later by limiting the PVs under conventional and characteristics modelling function of idioms, IPVs can be identified and served as the primary data. The final phase of the analysis wants to see how lexical interpretation, relying on Oxford Advanced Learner’s Dictionary 8th Edition (OALD 8thed), and Halidayan contextual variability (field, tenor and mode) help classifying and explaining the meanings of the IPVs. Finally it is expected that this paper can offer appropriate logical and contextual interpretations of the IPVs. This way, by watching the HPDH, learners of English can gain better understanding of the movies and, more importantly, better knowledge of IPVs as inseparable part of their competence of EFL.Keywords: HPDH, IPVs, lexical interpretation, contextual variability, contextual interpretations